Dendrimers Fundamentals and Applications - Maria Simonescu, Claudia (IntechOpen, 2018)
Dendrimers are defined as nanoscale macromolecules having a particular architecture consisting of treelike arms or branches. They are characterized by special properties that make them promising candidates in medicine, biology, materials science, synthetic organic chemistry, biotechnology, environmental engineering, optics, electronics, catalysis, electrochemistry, photochemistry, and sensors and even for production of cosmetics and personal care products. The dendrimers research field is growing day by day, and scientists are exploring new synthesis and functionalization methods in order to improve and to determine new properties and thus new applications. The main purpose of this book is to highlight the issues regarding properties and applications of dendrimers in the field of biology, medicine, liquid crystal devices, electronics, quantum devices, and self-healing technology.